Redistribuição de momentos fletores em estruturas hiperestáticas - Silva, Paulo José Chaves Araújo e (1977)
Theoretical and experimental work on the application of plastic analysis to statically indeterminate reinforced concrete structures are presented herein. Fourteen two-span contiuos beams were tested to failure. These beams were dimensioned according to bending moment diagrams differing in 15% and 25% from the bending moment diagram obtained from elastic analysis, at the sections of maximum bending moments. In order to determine the plastic rotation capacity of the plastic hinges, twelve simple supported single span beams were also tested to failure. These beams had the cross section and the reinforcement identical to those of the critical section of the corresponding statically indeterminate beam, and the span equal to the distance between the points of null bending moment. The behavior of the statically indeterminate beams showed a perfect adaptation of these beams to the adopted bending moment diagrams. Considerations are made about different existing methods of calculating the rotation capacity of reinforced concrete plastic hinges. Particular attention is given to the non-linear behavior of reinforced concrete.